Literary big data powered by libraries: reflections on annotation, cataloging, discovery, and recommendation infrastructures for narrative fiction - Saorín, Tomás (Anuario ThinkEPI, 2021)
Abstract: This work explores the relationships between the field of literary studies based on data inspired by the í¬distant readingí® school and the digital humanities and the activity of libraries and other agents of the book sector in the ecosystem of recommendation and discovery of readings. Projects for enriching catalogues and description resources about literary fiction are presented, such as OCLC FictionFinder and Kirjasampo, within the framework of transmedia and open metadata, understood in relation to the practices of digital content consumption platforms such as Netflix or Amazon Prime Video. Besides, other practices of annotation and editing of literary texts are outlined. Finally, I explain opportunities to develop digital Library Laboratories supported by open data infrastructures such as Wikidata for the enriched description past and present of narrative fictions in a collaborative way, to enable projects and services for the discovery of related readings.
Keywords: Reader's advisory; Genrification; Literature; Metadata; Fictional universes; Discovery; Transmedia; Cataloguing; Wikidata; Fiction; Library Labs